Mental and Physical Health Consequences of the September 11, 2001 (9/11) Attacks in Primary Care: A Longitudinal Study. Issue 1 (14th January 2013) - Neria, Yuval; Wickramaratne, Priya; Olfson, Mark; Gameroff, Marc J.; Pilowsky, Daniel J.; Lantigua, Rafael; Shea, Steven; Weissman, Myrna M.
<x xml:space="preserve">Abstract</x> The magnitude of the September 11, 2001 (9/11) attacks was without precedent in the United States, but long‐term longitudinal research on its health consequences for primary care patients is limited. We assessed the prevalence and exposure‐related determinants of mental disorders, functioning, general medical conditions, and service utilization, 1 and 4 years after the 9/11 attacks, in an urban primary care cohort (N = 444) in Manhattan. Although the prevalence of posttraumatic stress disorder (PTSD) and levels of functional impairment declined over time, a substantial increase in suicidal ideation and missed work was observed. Most medical outcomes and service utilization indicators demonstrated a short‐term increase after the 9/11 attacks (mean change of +20.3%), followed by a minor decrease in the subsequent year (mean change of −3.2%). Loss of a close person was associated with the highest risk for poor mental health and functional status over time. These findings highlight the importance of longitudinal assessments of mental, functional, and medical outcomes in urban populations exposed to mass trauma and terrorism.